Reuse of wastewater from pulp industry for the optimization of fungal xylanase production - Queiroz-Fernandes, Geisiany Maria de; Martins, Bruna Letícia; Rustiguel, Cynthia Barbosa (Acta Scientiarum. Biological Sciences, 2017)
The production of enzymes using agro-industrial waste is a low cost alternative for the reuse of byproducts, with the subsequent impact decrease on the environment. Current analysis produced xylanase using fungus Aspergillus niger, with two types of wastewater generated during the pulp chemical bleaching phase as inducers. Xylanase was produced by submerged liquid fermentation and factorial design optimized parameters that influence production (concentration of wastewater and production period). Initial culture conditions (pH, temperature and agitation) were optimized independently. Alkaline wastewater was more effective than acidic wastewater for the induction of xylanase in optimized conditions: 50% of culture medium, 7-day production, 30°C, pH 6.0 and agitation at 160 rpm. Despite different results, acidic and alkaline wastewaters induced xylanase production by A. niger when employed in concentrations lower than or equal to 50% of culture medium and in the most optimal conditions described above. Alkaline wastewater is highlighted as the most efficient for such production.